Transformasi Algoritmik dalam Sistem Penegakan Hukum Indonesia: Tantangan Yuridis Penggunaan Artificial Intelligence pada Era Society 5.0 - Robert Sangkala; Ida Komala; Satria Ari Wibowo; Roif Roif; Ali Asari; Windi Setiawan; Firman Adi Candra (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
Artificial Intelligence technology has significantly influenced the development of legal systems and law enforcement practices in Indonesia. The implementation of Artificial Intelligence in legal services offers efficiency, accuracy, and easier access to legal information. However, the use of Artificial Intelligence also creates legal and ethical challenges related to accountability, privacy, and legal certainty. This study aims to analyze the development of Artificial Intelligence in the Indonesian legal system. The research uses a normative juridical method with statutory and conceptual approaches. The findings reveal that Artificial Intelligence can improve the effectiveness of legal services and judicial administration. Nevertheless, Indonesia still lacks comprehensive regulations regarding the use of Artificial Intelligence in legal practice. Therefore, adaptive legal policies and stronger supervision mechanisms are required to ensure responsible technological implementation.